2015
DOI: 10.1007/s12026-015-8709-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study for identifying systemic biomarkers that correlate with pain response in patients with intervertebral disc disorders

Abstract: Molecular events that drive disc damage and low back pain (LBP) may precede clinical manifestation of disease onset and can cause detrimental long-term effects such as disability. Biomarkers serve as objective molecular indicators of pathological processes. The goal of this study is to identify systemic biochemical factors as predictors of response to treatment of LBP with epidural steroid injection (ESI). Since inflammation plays a pivotal role in LBP, this pilot study investigates the effect of ESI on system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 66 publications
2
38
1
1
Order By: Relevance
“…Per protocol, we excluded women of childbearing age and did not evaluate for factors that may influence biomarkers in the spine such as the presence of spondylolisthesis and dynamic instability, this may limit generalizability. Although we analyzed a broad spectrum of biomarkers, we did not include recently developed inflammatory biomarkers that may be more specific to IVD degeneration 40, 41 . Despite these limitations we found a difference in biomarker levels between distinct phenotypes of spine degeneration that potentially reflect a difference in pathophysiology of these important spine structures.…”
Section: Discussionmentioning
confidence: 99%
“…Per protocol, we excluded women of childbearing age and did not evaluate for factors that may influence biomarkers in the spine such as the presence of spondylolisthesis and dynamic instability, this may limit generalizability. Although we analyzed a broad spectrum of biomarkers, we did not include recently developed inflammatory biomarkers that may be more specific to IVD degeneration 40, 41 . Despite these limitations we found a difference in biomarker levels between distinct phenotypes of spine degeneration that potentially reflect a difference in pathophysiology of these important spine structures.…”
Section: Discussionmentioning
confidence: 99%
“…(11, 12, 98100) More recently, serum biomarkers have been reported that vary with diagnosis. (101, 101, 101, 101, 102, 102) In particular, serum levels of IL-6 were significantly higher in subjects with LBP compared with control subjects. (101, 102) Novel treatments targeting inflammation are being pursued.…”
Section: Role Of Inflammation In Ivd Degeneration and Back Painmentioning
confidence: 98%
“…(101, 101, 101, 101, 102, 102) In particular, serum levels of IL-6 were significantly higher in subjects with LBP compared with control subjects. (101, 102) Novel treatments targeting inflammation are being pursued. (103, 104) The high levels of proinflammatory mediators found in disc tissue from patients undergoing fusion for discogenic back pain suggest that production of proinflammatory mediators within the IVD may be a major factor in the genesis of a painful lumbar disc.…”
Section: Role Of Inflammation In Ivd Degeneration and Back Painmentioning
confidence: 99%
“…62 In a subsequent study, a more comprehensive profile was performed, which found that levels of many proinflammatory cytokines and growth factors were higher in stenosis and degenerative disc patients compared with disc herniation patients. 79 These factors included IL-2, IL-3, IL-8, hepatocyte growth factor (HGF), IFN-␣2, leukemia inhibitory factor, monocyte chemoattractant protein 3 (MCP-3), and TNF-␤. The use of diagnostic profiling or biomarker panels may serve to enhance the specificity and accuracy of diagnosis.…”
Section: T H 17 Cells Exert Proinflammatory Effects While T Reg Cellmentioning
confidence: 99%
“…On the other hand, disc herniation patients had an improvement in pain that correlated with decreases in factors that participate in hematopoiesis (SCGF-␤ and GM-CSF), nociception (SCF and IFN-␣2), and inflammation (IL-6, IL-10, IL-18, IL-2R␣, and IL-12p40). 79…”
Section: Biomarkers and Response To Treatmentmentioning
confidence: 99%